O uso do programa scratch na abordagem dos conceitos iniciais de cinemática para alunos do 1º ano do ensino médio - Farias, Fabrício de Oliveira (2016)
In this work we present a study on the use of animations in teaching activities in physical education, referring to the initial concepts of kinematics. The objective of this research is to apply the initial concepts of kinematics that is studied in the 1st year of high school more dynamic, contextualized and with the help of a software, but with the participation of students in order to make the enhanced learning. Scratch program will feature the technology (software) used to mediate the teaching of initial concepts of kinematics and become the most promising learning. The activities proposed in this study are based on the constructivist theory of Jerome Bruner which considers education for discovery and a proposed curriculum spiral format in which the content is proposed for surface and in-depth manner according to student learning. The participants were twelve students in a class of 1st year of high school of electrical engineering course in reliance belonging to the Federal Institute of Amazonas, Manaus-center campus. The instruments of data collection of this research were a pretest, two lists of exercises as the class script, a post test and two educational-methodological questionnaires. The conclusions derived from the vision of the students point out that the study of the initial concepts of kinematics, using animations and predefined physical concepts: (i) approached the theoretical knowledge of physics with everyday life, promoting learning, (ii) provided connections between the problem situations presented in the animations and physical content through interactivity, (iii) They aroused the pleasure of learning, and (iv) had innovative character, making interesting physics classes and different traditional classes. It is noteworthy that the vast majority of students considered useful lessons from this approach, and that the conceptual difficulties decreased intensely.